Salivary levels of antimicrobial peptides Hnp 1-3, Ll-37 and S100 in Behcet's disease - MUMCU, GONCA; DİRESKENELİ, RAFİ HANER; ERGUN, SAFİYE ATLAS TÜLİN; CİMİLLİ, ZÜHRE HALE (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
Background: Oral ulcer is the cardinal clinical sign and increased neutrophilic activity is a part of the pathogenesis in Behcet's disease (BD). Saliva, as a part of the innate immune response, contains antimicrobial peptides (AMPs) that are derived from both oral epithelial cells and neutrophils. The aim of this study was to investigate the associations between salivary levels of AMPs HNP 1-3, LL-37 and S100 and disease course in patients with Behcet's disease (BD). Methods: Fifty-three patients with BD and 44 healthy controls (HC) were included in the study. Disease severity score reflecting organ involvement was calculated. Salivary HNP 1-3, LL-37 and S100 levels were measured in unstimulated saliva samples by ELISA. Results: Salivary HNP 1-3 and S100 levels in BD patients (2715.2 +/- 1333.4 mu g/ml and 430.6 +/- 203.9 mu g/ml) were significantly higher compared to HC (1780.6 +/- 933.2 mu g/ml and 365.3 +/- 84.7 mu g/ml) (p = 0.000 and p = 0.004, respectively). Although LL-37 levels were also higher in BD than HC (190.9 +/- 189.1 vs 143.1 +/- 128.9 ng/ml), no significant difference was observed (p = 0.53). Salivary HNP 1-3 and LL-37 levels were associated with the severity of BD (mild disease: 1975.1 +/- 1174.2 mu g/ml and 115.9 +/- 109.4 ng/ml vs severe disease: 2955.7 +/- 1305.6 mu g/ml and 215.3 +/- 203.8 ng/ml, p = 0.020 and p = 0.031, respectively). Salivary LL-37 levels also correlated with the number of monthly oral ulcers (r = 0.5 p = 0.000). Conclusion: An increase in salivary HNP 1-3 and S100 levels might be associated with enhanced local and systemic innate responses in BD. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Behget disease; Saliva and HNP 1-3; EXPRESSION; NEUTROPHILS; CARIES; CELLS; PATHOGENESIS; ASSOCIATION; ACTIVATION; SEVERITY; PROTEINS; HEALTH